2011
DOI: 10.3758/s13414-011-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent motion enhances visual rhythm discrimination in infancy

Abstract: Many studies have demonstrated that infants exhibit robust auditory rhythm discrimination, but research on infants’ perception of visual rhythm is limited. In particular, the role of motion in infants’ perception of visual rhythm remains unknown, despite the prevalence of motion cues in naturally occurring visual rhythms. In the present study, we examined the role of motion in 7-month-old infants’ discrimination of visual rhythms by comparing experimental conditions with apparent motion in the stimuli versus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Although many prior studies have shown that children ( Drake et al, 2000 ), and even infants ( Haith et al, 1988 ; Colombo and Richman, 2002 ; Philips-Silver and Trainor, 2005 ; Werner et al, 2009 ; Winkler et al, 2009 ; Brandon and Saffran, 2011 ), process the temporal information inherent in isochronous rhythms, we demonstrate that children can then use this temporal information to guide and optimize their responses to temporally predictable events. In adults, the temporal predictability of isochronous or rhythmic sequences orient attention to moments in time that are in phase with the entraining rhythm, thereby optimizing processing of stimuli appearing at those precise moments ( Doherty et al, 2005 ; Martin et al, 2005 ; Correa and Nobre, 2008 ; Ellis and Jones, 2010 ; Rohenkohl et al, 2011 ; Sanabria et al, 2011 ; de la Rosa et al, 2012 ; Miller et al, 2013 ; Cutanda et al, 2015 ).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although many prior studies have shown that children ( Drake et al, 2000 ), and even infants ( Haith et al, 1988 ; Colombo and Richman, 2002 ; Philips-Silver and Trainor, 2005 ; Werner et al, 2009 ; Winkler et al, 2009 ; Brandon and Saffran, 2011 ), process the temporal information inherent in isochronous rhythms, we demonstrate that children can then use this temporal information to guide and optimize their responses to temporally predictable events. In adults, the temporal predictability of isochronous or rhythmic sequences orient attention to moments in time that are in phase with the entraining rhythm, thereby optimizing processing of stimuli appearing at those precise moments ( Doherty et al, 2005 ; Martin et al, 2005 ; Correa and Nobre, 2008 ; Ellis and Jones, 2010 ; Rohenkohl et al, 2011 ; Sanabria et al, 2011 ; de la Rosa et al, 2012 ; Miller et al, 2013 ; Cutanda et al, 2015 ).…”
Section: Discussionmentioning
confidence: 53%
“…Although children in this age range can estimate stimulus duration as well as adults ( McCormack et al, 2005 ; Droit-Volet and Coull, 2015 ; Droit-Volet, 2016 ), it appears that they are not yet able to use this information to make temporal predictions in order to optimize behavior. Yet previous studies have shown that even young infants derive temporal expectations from isochronous or rhythmic sequences of stimuli ( Haith et al, 1988 ; Colombo and Richman, 2002 ; Philips-Silver and Trainor, 2005 ; Werner et al, 2009 ; Winkler et al, 2009 ; Brandon and Saffran, 2011 ). In Study 2 therefore, we further increased the exogenous temporal information conveyed by the temporal cue by presenting cues in an isochronous sequence.…”
Section: Study 1: Temporal Information Conveyed By Cue Durationmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the vast literature on modality differences in temporal perception, the advantages of moving over static visual stimuli have been less explored in perception than in synchronization. It is known that infants discriminate moving visual stimuli more accurately than static ones (Brandon and Saffran, 2011), but comparisons between discontinuously moving visual stimuli (rotating bars, changing to non-contiguous spatial positions, as in Hove et al, 2013a) and auditory ones (beeps) showed an advantage of the auditory modality (Grahn, 2012). Bouncing balls (continuously moving stimuli) have not yet been tested as potentially optimal visual stimuli, and the powerful ball effect has not been fully tested in the perceptual domain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have found that newborn infants can distinguish between different language classes on the basis of their rhythmic/prosodic attributes (Nazzi, Bertoncini & Mehler, 1998) and that infants as young as 2 months of age can perceive the rhythmical characteristics of auditory patterns (Chang & Trehub, 1977a, 1977bDemany, McKenzie & Vurpillot, 1977;Demany, 1982;Trehub & Thorpe, 1989). In addition, studies have found that infants as young as 4 months of age can perceive the temporal features of auditory, visual, and audiovisual sequences (Brandon & Saffran, 2011;Lewkowicz, 1988aLewkowicz, , 1988bLewkowicz, , 1992bLewkowicz, , 2003Lewkowicz & Marcovitch, 2006;Pickens & Bahrick, 1997) and that they can perceive the relationship between auditory and visual information on the basis of temporal information (Allen et al, 1977;Lewkowicz, 1986Lewkowicz, , 1992aLewkowicz, , 2010Mendelson, 1986;Scheier, Lewkowicz & Shimojo, 2003). Finally, it has been found that temporal discrimination increases in precision during infancy (Brannon, Suanda & Libertus, 2007).…”
Section: Introductionmentioning
confidence: 99%